Bureaucratic exercise? Education for sustainable development in Taiwan through the stories of policy implementers. Issue 7 (5th May 2021) - Huang, Ying-Syuan (Elaine); Harvey, Blane; Asghar, Anila
Abstract: Despite eight years of strong national support, Taiwan's Education for Sustainable Development (ESD) has generated limited enthusiasm for sustainable development, and is even turning some policy implementers into ESD skeptics. In one of the first attempts to study the work of policy implementers within Taiwan's ESD initiatives, this study examines links between national policy and practice in educational settings. Drawing on interviews with thirty policy implementers and about seventy hours of observation in the field, we found that Taiwan's nationwide ESD program has failed to prompt meaningful actions that address unsustainable development. Moreover, the government's instrumental approach to promoting a system-wide ESD program in the face of inaction on sustainability concerns in other sectors risks reducing this work to a symbolic, or bureaucratic exercise. Consequently, people's attention has been drawn away from searching and collectively reflecting on the deep leverage points for a sustainability transition. These findings have important implications for future initiatives aimed at reforming education policy and implementing mandatory ESD curricula.